Meningkatkan Kemampuan Kognitif Pada Anak Usia Dini - Laelawati, Ida (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2023)
The background of the problem that underlies the research at Nurul Falah Al Yaman Kindergarten Tegal Regency is the learning outcomes, especially in cognitive abilities are still low, it is because the teacher in teaching using methods and media that are less interesting and less creative and tend to be boring. The purpose of this study was to improve the cognitive abilities of Nurul Falah Al Yaman kindergarten students, especially in sorting objects with demonstration methods using picture media. Through the activity of sorting objects with the demonstration method using image media so that children can be more active in learning so that learning feels more fun so that children are more enthusiastic in participating in learning. This research was conducted in 2 cycles and each cycle consisted of 4 stages, namely planning, implementation, observation, and reflection. At the end of each lesson students are given worksheets to do. From cycle I to cycle II obtained an increase in cognitive abilities in kindergarten students Nurul Falah Al Yaman Yamansari Village Lebaksiu District Tegal Regency is an increase from 69% increased to 92%, thus it can be concluded that the activity of sorting objects with demonstration methods and using image media can improve cognitive abilities of kindergarten students Nurul Falah Al Yaman Tegal Regency.